Genome-wide association study for vascular aging highlights pathways shared with cardiovascular traits in Koreans - Ahn, JaeKyoung; Jeong, Hankyeol; Seo, Bo-Gyeong; Park, Ki-Soo; Hwangbo, Cheol; Kim, Han-Gyul; Koh, Jin-Sin; Kim, Jaemin (Frontiers in Cardiovascular Medicine, 2022)
Vascular aging plays a pivotal role in the morbidity and mortality of older people. Reactive hyperemia index (RHI) detected by pulse amplitude tonometry (PAT) is a noninvasive measure of vascular endothelial function and aging-induced pathogenesis of both microvascular and macrovascular diseases. We conducted a genome-wide association study (GWAS) to comprehensively identify germline genetic variants associated with vascular aging in a Korean population, which revealed 60 suggestive genes underlying angiogenesis, inflammatory response in blood vessels, and cardiovascular diseases. Subsequently, we show that putative protective alleles were significantly enriched in an independent population with decelerated vascular aging phenotypes. Finally, we show the differential mRNA expression levels of putative causal genes in aging human primary endothelial cells via quantitative real-time PCR. These results highlight the contribution of genetic variants in the etiology of vascular aging and the link between vascular aging and cardiovascular traits.